That Camden summer - Spencer, LaVyrle (Thorndike, Me. : G.K. Hall, 1996)
When a fiercely independent young woman returns with her three daughters to her hometown of Camden, Maine, after divorcing her philandering husband, she finds a less-than-hospitable welcome. But she's about to show an entire town what one good woman can do.
"G.K. Hall large print core collection"--T.p. verso.
70383
Keywords: Large type books; Women -- History -- Fiction. -- 20th century -- Maine; Divorced mothers -- Fiction. -- Maine; Maine -- Fiction; Historical fiction; Domestic fiction